1993
DOI: 10.1557/jmr.1993.3176
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-hydrothermal processing for synthesis of electroceramic powders

Abstract: Microwave-hydrothermal processing has so far been used only to dissolve inorganic solids for chemical analysis. We report herein the use of microwave-hydrothermal processing to synthesize various ceramic powders in binary and polynary systems. We describe the synthesis of some electroceramic powders such as BaTiO3, SrTiO3, Sr0.5Ba0.5TiO3, PbTiO3, BaZrO3, SrZrO3, Pb(Zr0.52Ti0.48)O3, and pyrochlore phases with the Pb(Mg1/3Nb2/3)O3 and Pb(Zn1/3Nb2/3)O3 compositions by this novel microwave-hydrothermal processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(70 citation statements)
references
References 18 publications
2
66
0
Order By: Relevance
“…It has been reported recently that the microwave synthesis methods could provide an efficient way to control phase selectivity as well as fast crystallization. 11 Komarneni et al 12,13 reported the microwave-hydrothermal synthesis of BiFeO 3 at 194°C for 2 h, but the product was highly crystalline agglomerated particles. Until now there is no other report of microwave synthesis of BiFeO 3 perovskite nanomaterials.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%
“…It has been reported recently that the microwave synthesis methods could provide an efficient way to control phase selectivity as well as fast crystallization. 11 Komarneni et al 12,13 reported the microwave-hydrothermal synthesis of BiFeO 3 at 194°C for 2 h, but the product was highly crystalline agglomerated particles. Until now there is no other report of microwave synthesis of BiFeO 3 perovskite nanomaterials.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%
“…The first studies about microwave-assisted hydrothermal crystallization were conducted by Komarneni et al [44] [45]. In these studies, authors observed several advantages over the conventional technique such as a significant reduction of reaction times and, in some cases, the formation of different crystalline phases than those obtained by the conventional hydrothermal route.…”
Section: Microwave-assisted Hydrothermal Crystallizationmentioning
confidence: 99%
“…Preliminary evidences of the microwave athermal effects appeared from some experiments on microwave-hydrothermal synthesis of ceramic powders 34,[49][50][51] , in which microwave-induced kinetic acceleration was demonstrated in comparison to conventional synthesis with nearly identical hydrothermal (temperature and pressure) conditions. These studies, however, should be refined since they did not give quantitative evaluations on the microwave effects.…”
Section: Identification and Evaluation Of Microwave Athermal Effectmentioning
confidence: 99%